Abu Hanifa and Hadith - ÜNAL, İsmail Hakkı; TASHTANOVA, Aizada (Scientific Journal of Faculty of Theology, 2020)
One of the most popular schoolars among the muslims in İslamic history was Abu Hanifa. The place where he was born, played the important rule in his understanding of İslamic law. İn choosing, analysing and in using in judgment the Prophet Muhammad’s hadiths, he had own methods for what he had been critisized widely by muhaddiths. İn this article we will try to exlpain in short, Abu Hanifa’s understanding of prophet’s hadiths and his mothodology in choosing and analysing the riwayats.